Fears and fallacies: Doctors' perceptions of the barriers to medical innovation. (December 2019) - Elliott, Tracey; Miola, Jose; Samanta, Ash; Samanta, Jo
In 2014, Lord Saatchi launched his ultimately unsuccessful Medical Innovation Bill in the UK. Its laudable aim was to free doctors from the shackles that prevented them from providing responsible innovative treatment. Lord Saatchi's principal contention was that current law was the unsurmountable barrier that prevented clinicians from delivering innovative treatments to cancer patients when conventional options had failed. This was because doctors feared that they might be sued or tried and convicted of gross negligence manslaughter if they deviated from standard practice. Concerns about fear of the law and potential negative effects on medical practice are not new. Fear of litigation has been suggested as the reason for doctors practising "defensive medicine, " by opting for treatments regarded as "grievance-resistant, " rather than clinically indicated, for example, by ordering diagnostic tests or performing certain procedures, which are not strictly medically necessary. Whilst this claim is plausible and apparently accepted by the courts, there is limited empirical evidence in support of it so far as practitioners in the UK are concerned. In this paper, we report on our empirical research which provides a snapshot of medical opinion to begin to rectify this gap. We ran focus groups of different medical specialties, asking what these medical practitioners thought the barriers to medical innovation to be. We found that fear of the law was not the principal barrier to be lowered, and that the answer was far more multifaceted.